2017
DOI: 10.1016/j.hfc.2017.05.002
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac Clocks and Preclinical Translation

Abstract: Circadian rhythms are fundamentally important for cardiovascular health, including heart rate, blood pressure, and molecular gene and protein responses. Rhythms also play a direct role in the pathophysiology of heart disease, such as in the timing of onset and severity of myocardial infarction, sudden cardiac death, ventricular arrhythmias, and stroke. Importantly, a flurry of new studies reveals translational applications for circadian biology to clinical medicine, and especially cardiology. Circadian medicin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(22 citation statements)
references
References 150 publications
0
20
0
2
Order By: Relevance
“…In addition to myocardial infarction, circadian rhythm variations also influence the onset of other vascular events, including stroke and venous thromboembolism (VTE) . Numerous studies have confirmed that the onset of stroke is predominant in the morning, between 6 am and noon, when circulating cortisol levels are also at its peak . The incidence of stroke steadily declines during the remainder of the day and is least likely to occur in the late evening, coinciding with the decline in circulating cortisol levels .…”
Section: Discussionmentioning
confidence: 99%
“…In addition to myocardial infarction, circadian rhythm variations also influence the onset of other vascular events, including stroke and venous thromboembolism (VTE) . Numerous studies have confirmed that the onset of stroke is predominant in the morning, between 6 am and noon, when circulating cortisol levels are also at its peak . The incidence of stroke steadily declines during the remainder of the day and is least likely to occur in the late evening, coinciding with the decline in circulating cortisol levels .…”
Section: Discussionmentioning
confidence: 99%
“…Non-dipping was more prevalent in African-Americans. For an excellent in-depth review in the area of the cardiac clock and its implications for human health, see Mistry et al [39].…”
Section: Mechanisms Of Circadian Bp Regulation In Humansmentioning
confidence: 99%
“…Coronary artery disease frequently leads to myocardial infarction (MI; heart attack), and subsequently the development of heart failure (HF), for which there is no cure. Previously, clinical studies revealed that the circadian system underlies healthy cardiovascular physiology, for example, driving 24-h day and night rhythms in heart rate [5], blood pressure [6], and timing of onset of adverse cardiovascular events [7][8][9][10][11]. Most recently, experimental studies by our group and others show that the circadian system also plays a critical role in remodeling in cardiovascular disease.…”
Section: Introductionmentioning
confidence: 95%